The Effect of the Kinetic Sand Play Method on Fine Motor and Cognitive Development in Preschool Children - Reni Anggraeni; Dini Mariani; Novi Enis Rosuliana (Jurnal Keperawatan Olahraga, 2025)
Background: Fine motor and cognitive skills are essential aspects of preschool children's development, as they are closely related to learning readiness, independence, and self-confidence. Aims: To determine the effect of kinetic sand play on the improvement of fine motor and cognitive development in children aged 3–5 years. Methods: This research applied a quantitative approach with a quasi-experimental design, specifically the two-group pretest-posttest with control group design. The population consisted of 80 children, and 36 were selected as samples using purposive sampling, with 18 children in both the intervention and control groups. Data were collected using standardized observation sheets and analyzed using the Paired t-test and Independent t-test. Results: The results showed a significant difference between pretest and posttest scores in the intervention group p = 0.000 (< 0.05), as well as a significant difference between the intervention and control groups after the intervention p = 0.000 (< 0.05). Conclusion: It can be concluded that kinetic sand play has a positive effect on improving children's fine motor and cognitive development. This activity is recommended to be implemented as an educational stimulus in early childhood education settings, as it is enjoyable, safe, and capable of stimulating children's holistic development.